Decision Support System for Foundation Beneficiaries Using the Simple Additive Weighting (SAW) Method - Herpendi; Manalu, Mamed Rofendy (Bahasa Indonesia, 2025)
The distribution of compensation funds for underprivileged students must be based on clear and objective selection mechanisms to ensure that assistance is allocated to the most deserving recipients. A Decision Support System (DSS) provides a systematic and efficient method to support this selection process. This research utilizes the Simple Additive Weighting (SAW) method to develop a DSS that ranks students based on predefined criteria such as parents’ income, family status, number of dependents, and academic achievement. The ranking results indicate that Farhan Rifai scored the highest (0.8), followed by Sidratul Muntaha (0.7666), demonstrating the method's effectiveness in supporting fair compensation distribution.